Senior high school students thinking levels in permutation and combination using solo taxonomy - Appiah, Stephen Junior; Amoah, Emmanuel Kojo; Adjei, Emmanuel Antwi; Akayuure, Peter (Asian Journal of Contemporary Education, 2025)
Although the Ghanaian mathematics curriculum emphasizes critical thinking as a core competence, students still appear to lack this skill. In this mixed-method study, the Structure of the Observed Learning Outcome (SOLO) taxonomy was used to assess senior high school students’ thinking levels in permutation and combination. A sample of 256 males and 104 females was randomly selected from three senior high schools for the study. The data were collected using tests and interviews, and analyzed descriptively and inferentially using Kruskal-Wallis tests. The results showed that while only one-fifth of the students reached the higher relational and extended abstract thinking levels, the majority (73.9%) remained at the lower levels of pre-structural, uni-structural, and multi-structural thinking. These students struggled to apply basic counting and multiplication principles in solving higher-order thinking problems. The Kruskal-Wallis H test further revealed statistically significant differences in thinking levels across the study programmes. General Science students demonstrated the highest thinking levels, followed by General Agriculture and Business students. The study concluded that students’ thinking levels in permutation and combination were low. It is recommended that teachers, textbook authors, and curriculum developers adopt representations and activity-based teaching strategies to help students develop a conceptual understanding of the topic.